The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1088/0031-8949/90/6/068005
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic solitons in degenerate relativistic electron–positron plasma

Abstract: The existence of soliton-like electromagnetic (EM) distributions in a fully degenerate electronpositron plasma is studied applying relativistic hydrodynamic and Maxwell equations. For circularly polarized wave it is found that the soliton solutions exist both in relativistic as well as nonrelativistic degenerate plasmas. Plasma density in the region of soliton pulse localization is reduced considerably. The possibility of plasma cavitation is also shown.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
(54 reference statements)
0
37
0
Order By: Relevance
“…to the degenerate electrons. The electron dynamics for both components will be described by the appropriate relativistic fluid equations [ (Pino et al 2010), (Berezhiani et al 2015a), (Berezhiani et al 2015b)]: the continuity…”
Section: Model Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…to the degenerate electrons. The electron dynamics for both components will be described by the appropriate relativistic fluid equations [ (Pino et al 2010), (Berezhiani et al 2015a), (Berezhiani et al 2015b)]: the continuity…”
Section: Model Equationsmentioning
confidence: 99%
“…Consequently, the degeneracy pressure may easily dominate the thermal one [see e.g. (Shapiro & Teukolsky 1973), (Michel 1982;Berezhiani et al 2015a), (Berezhiani et al 2015b;Shatashvili et al 2016) and references therein]. Relativistic outflows/jets, often, come out of these compact objects.…”
mentioning
confidence: 99%
“…Applying this relation, and after straightforward algebra (see e.g. [31][32][33]), the equation of motion for degenerate electron fluid reduces to:…”
Section: Modelmentioning
confidence: 99%
“…In a series of papers [5]- [8], where authors examined the nonlinear character of interactions of plasma waves and high frequency EM waves it was found that ✩ Fully documented templates are available in the elsarticle package on CTAN.…”
Section: Introductionmentioning
confidence: 99%